Evaluation of the Impact of the COVID-19 Pandemic on the Incidence of Cancer: A Comparative Analysis between the Years 2018 and 2022 - Riquelme-Heras, Hector; Zarate-Escamilla, Marcelo; Gutierrez-Herrera, Raul; Saenz-Saucedo, Isauro; Ordoñez-Azuara, Yeyetzy; Nielsen-Fonseca, Salma (British Journal of Healthcare and Medical Research, 2025)
Background: The SARS-CoV-2 pandemic has caused unprecedented medical, social, and economic challenges, resulting in lockdowns, travel restrictions, social isolation, and distancing measures. Some research studies have shed some light on how this pandemic has influenced cancer screening and treatment services, highlighting the urgent need to continue to assess incidence rates during this period. Objective: To evaluate the incidence of cancer pre and post-COVID-19 Pandemic in a highly specialized hospital. Methods: Descriptive, Cross-sectional, Retrospective Study. We studied all biopsy reports of cancer from the highly specialized hospital Pathology Department between 2018 and 2022. Results: The results of 8804 biopsies were analyzed. In 2018, 4379 were examined, of which 1622 were benign specimens, and 2757 (62.95%) were diagnosed with malignancy. In 2022, 4425 were studied, of which 1209 were diagnosed with benignity and 3216 (72.68%) were malignant. Conclusion: Compared to the pre-pandemic year and the post-pandemic year, reports of biopsies with malignancy diagnoses increased.